Factors affecting the decision-making of selected middle-income rural mothers on shifting from breastfeeding to formula feeding - Almoite, Abygaile Gelacio; De Guzman, Ines A. (Quezon City UP College of Home Economics, 2012)
The Philippine population continues to grow in a fast pace and the number of infants is also increasing. A significant number of studies on the beneficial effects of breastfeeding have been conducted and the positive effects have been disseminated. However, poor infant feeding practices remain a key problem. This inspired the researcher to conduct a study to be able to: describe infant feeding practices of middle income rural mothers in terms of style and duration; determine how middle-income rural mothers utilize their breastfeeding knowledge and how it affects their feeding practices; identify reasons for the shift from breastfeeding to formula feeding; and find out possible knowledge and practice enhancement topics for mothers. Random sampling was used in choosing the 36 respondents from Cabangan, Zambales. The Chi-square test was used to see the correlation between the stated factors such as age, income, education, nature of work, and their influence on the feeding practices of the mothers. The study used 0.10 as the standard level of significance. Based on the results, all the respondents planned to breastfeed their infants. However, formula feeding rate was still higher. The duration of breastfeeding for majority of of the breastfeeding mothers was more than six months. Majority of the respondents who used mixed feeding scored high in the knowledge test. The knowledge test on breastfeeding advantages to infants obtained a higher percentage of correct answers than advantages to mothers. The primary reason for shifting infant feeding practice was work. Also, the respondents initiated formula feeding because they think it provides the right amount of milk for their infants.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Infant feeding -- Philippines; Breastfeeding -- Philippines